A kind of high-durability polarizer glue and preparation method thereof
By using a combination of polyvinyl alcohol Z-410, boric acid solution and ethanol aqueous solution, the problem of poor water resistance of existing polarizer glue is solved, high durability and good water resistance are achieved, and it is suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202411898446.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
AI Technical Summary
The existing polarizer glue has poor water resistance, resulting in poor durability in the double 85 reliability experiment and black edges are prone to appear around.
Polyvinyl alcohol Z-410, boric acid solution and ethanol aqueous solution are used as important components. By controlling the group distribution ratio and feeding speed, the molecular weight is increased and the molecular gap is reduced, and the water resistance and durability of the glue is improved.
The durability of the dual 85 reliability experiment was achieved for more than 1000 hours, and the surroundings did not turn black, which significantly improved the water resistance and durability of the polarizer.
Smart Images

Figure CN119736038A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optical polarizing elements, and in particular, relates to a highly durable polarizing film glue; in addition, the invention also relates to a preparation method of the highly durable polarizing film glue. Background Art
[0002] High-durability polarizers must meet the dual 85 reliability test (85°C, 85RH%) for 1000h with no significant changes in optical indicators and appearance. Their superb weather resistance is widely used in corresponding smart displays. There are many ways to make high-durability polarizers. The use of PVA glue plays an important role in improving its durability. Improving PVA water-based glue is also a way to improve its durability.
[0003] Chinese patent CN 113502136A discloses a glue for polarizer and its preparation method, which is made of the following components by weight: 80-92 parts of deionized water, 3-5 parts of polyvinyl alcohol, 2-5 parts of SPM-01, 0.1-0.5 parts of anhydrous zinc chloride, 0.1-0.3 parts of concentrated hydrochloric acid, 0.025-0.042 parts of sodium hydroxide and 1-5 parts of glyoxal solution; in its preparation process, polyvinyl alcohol is first stirred and dissolved in deionized water, and a mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid, sodium hydroxide solution, glyoxal solution and SPM-01 are added, and stirred evenly to obtain the result. After the polarizer made of the glue disclosed in the patent is soaked in water at 80°C for 1 hour, the edge of the polarizer will appear obvious blackening (commonly known as PVA shrinkage), indicating that the high-durability polarizer made of this glue has poor water resistance. In addition, when the polarizer made of this glue is processed again, the reliability of the prepared product is also poor. During the double 85 reliability test for 500 hours, black borders will appear around it. Summary of the invention
[0004] The purpose of the present invention is to provide a highly durable polarizer glue on the basis of the prior art, which can solve the problem of poor water resistance of the current polarizer glue and improve the durability of the polarizer, so as to achieve a double 85 reliability test of more than 1000 hours without blackening on all sides.
[0005] The technical solution of the present invention is as follows:
[0006] A highly durable polarizer glue is prepared from the following components in parts by weight: 80-92 parts of deionized water, 3-5 parts of polyvinyl alcohol Z-410, 2-5 parts of SPM-01, 0.1-0.5 parts of anhydrous zinc chloride, 0.05-0.15 parts of concentrated hydrochloric acid, 0.025-0.042 parts of sodium hydroxide, 1-5 parts of glyoxal solution, 1-5 parts of boric acid solution and 1-2 parts of ethanol aqueous solution. In the preparation process, polyvinyl alcohol is firstly stirred and dissolved in deionized water, and a mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid, a sodium hydroxide solution, a glyoxal solution, SPM-01, a boric acid solution and an ethanol aqueous solution are added, and stirred evenly to obtain the glue.
[0007] The components of the polarizer glue provided by the present invention include deionized water, polyvinyl alcohol Z-410, SPM-01, anhydrous zinc chloride, concentrated hydrochloric acid, sodium hydroxide, glyoxal solution, boric acid solution and ethanol aqueous solution. In the process of preparing the glue, the component sodium hydroxide is mixed with other components in the form of sodium hydroxide solution to achieve better preparation effect, and the feeding speed of the sodium hydroxide can be controlled.
[0008] In a preferred embodiment, the preparation of the highly durable polarizer glue comprises the following steps: (1) stirring and dissolving polyvinyl alcohol Z-410 in deionized water at 25 to 35° C., and after stirring and dissolving, continuing to heat up to 85 to 95° C. and stirring; (2) cooling to 30 to 40° C., adding a prepared mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid, and stirring; (3) slowly dropping a prepared sodium hydroxide solution, and stirring; (4) adding glyoxal solution, and stirring; (5) adding SPM-01, and stirring evenly; (6) adding a prepared mixed solution of boric acid solution and ethanol aqueous solution, and stirring evenly to obtain the product.
[0009] For the high-durability polarizer glue of the present invention, the role of polyvinyl alcohol Z-410 is crucial. On the basis of Chinese patent CN 113502136A, polyvinyl alcohol Z-410 is used to replace polyvinyl alcohol Z-200. Its molecular weight is larger and the molecular gap is smaller, which makes it more difficult for water molecules to invade, thereby improving the water resistance and water resistance of the polarizer glue, achieving a double 85 reliability test of more than 1000 hours without blackening around.
[0010] In addition, in the process of preparing the highly durable polarizer glue of the present invention, boric acid solution is added to play a cross-linking role, and combined with polyvinyl alcohol Z-410, the molecular weight can be further increased and the gap between molecules can be reduced. In addition, due to the increase in molecular weight and the cross-linking effect, the solubility is reduced. Using ethanol aqueous solution as a solvent can improve the solubility and further improve the water resistance and water resistance of the polarizer glue.
[0011] In the process of preparing glue, the present invention also needs to control the feeding speed of sodium hydroxide, adjust the specific amount of sodium hydroxide added to the glue per unit time, so as to further control the polymerization time of the glue, and avoid the polymerization time of the glue being too short, which leads to the polymerization effect failure, low yield, poor water resistance and other problems after the prepared glue is used in the polarizer. In order to solve the problem of too fast feeding speed, sodium hydroxide is first prepared into a low-concentration sodium hydroxide solution, and the feeding speed can be controlled by slowly dropping to avoid the adverse effects caused by too fast feeding speed of sodium hydroxide. For the present invention, when preparing glue, the mass fraction of the low-concentration sodium hydroxide solution is controlled at 0.5-1%, which can be but not limited to 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, and preferably, the mass fraction of the sodium hydroxide solution is 0.8%.
[0012] In a preferred embodiment, the high-durability polarizer glue of the present invention is made of the following components in parts by weight: 82 to 88 parts of deionized water, 4 to 5 parts of polyvinyl alcohol Z-410, 2.5 to 3.5 parts of SPM-01, 0.25 to 0.35 parts of anhydrous zinc chloride, 0.08 to 0.12 parts of concentrated hydrochloric acid, 0.028 to 0.034 parts of sodium hydroxide, 2.5 to 3.5 parts of glyoxal solution, 3 to 4 parts of boric acid solution and 1.1-1.5 parts of ethanol aqueous solution.
[0013] In a more preferred embodiment, the high-durability polarizer glue of the present invention is made of the following components in parts by weight: 84 parts of deionized water, 4.5 parts of polyvinyl alcohol Z-410, 3 parts of SPM-01, 0.3 parts of anhydrous zinc chloride, 0.1 parts of concentrated hydrochloric acid, 0.03 parts of sodium hydroxide, 3.2 parts of glyoxal solution, 3.5 parts of boric acid solution and 1.37 parts of ethanol aqueous solution.
[0014] For the present invention, the polyvinyl alcohol Z-410 in the present invention is prepared by Nippon Synthetic Chemical Industry Co., Ltd.; SPM-01 is prepared by Nippon Synthetic Chemical Industry Co., Ltd.
[0015] In a preferred embodiment, the preparation of the highly durable polarizer glue comprises the following steps:
[0016] (1) Stir and dissolve polyvinyl alcohol Z-410 in deionized water at 25-35° C., and then continue to heat to 85-95° C. and stir;
[0017] (2) Cooling to 30-40°C, adding a mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid, and stirring;
[0018] (3) slowly add the prepared sodium hydroxide solution dropwise and stir;
[0019] (4) adding glyoxal solution and stirring;
[0020] (5) Add SPM-01 and stir evenly;
[0021] (6) Add the prepared mixed solution of boric acid solution and ethanol aqueous solution and stir evenly to obtain the product.
[0022] In a preferred embodiment, in step (1), polyvinyl alcohol Z-410 is dissolved in deionized water at 30°C by stirring.
[0023] Further, after stirring and dissolving, continue to heat to 90°C and stir for 0.5 to 3h;
[0024] Furthermore, stirring is performed for 1 to 2 hours.
[0025] In a preferred embodiment, in step (2), the temperature is lowered to 32° C., a mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid is added, and stirred; further, the stirring time is 30 to 60 minutes.
[0026] In a preferred embodiment, in step (3), the mass fraction of the sodium hydroxide solution is 0.5-1%, which may be but is not limited to 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%. More preferably, the mass fraction of the sodium hydroxide solution is 0.8%.
[0027] Furthermore, the stirring time is 30 to 60 minutes.
[0028] In a preferred embodiment, in step (4), the mass fraction of the glyoxal solution is 35-45%, which may be but is not limited to 35%, 36%, 38%, 39%, 40%, 41% or 45%. More preferably, the mass fraction of the glyoxal solution is 40%.
[0029] Furthermore, the stirring time is 30 to 60 minutes.
[0030] In a preferred embodiment, in step (5), SPM-01 is added and the stirring time is 30 to 60 minutes.
[0031] In a preferred embodiment, in step (6), the mass fraction of the boric acid solution is 0.15-0.25%, which may be but is not limited to 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24% or 0.25%. More preferably, the mass fraction of the boric acid solution is 0.18%.
[0032] In step (6), the mass fraction of the ethanol aqueous solution is 92-98%, which may be but is not limited to 92%, 93%, 94%, 95%, 96%, 97% or 98%. More preferably, the mass fraction of the ethanol aqueous solution is 95%.
[0033] Furthermore, the stirring time is 30 to 60 minutes.
[0034] In a preferred embodiment, the preparation of the highly durable polarizer glue provided by the present invention comprises the following detailed steps:
[0035] (1) Add deionized water to a beaker, keep it warm at 30°C and stir it evenly, then add polyvinyl alcohol Z-410 to the beaker in small amounts and multiple times until no lumps form. After adding, keep it warm at 30°C and stir it, then raise the temperature to 90°C and stir it for 1 to 2 hours; then cool it down to 32°C in a water bath;
[0036] (2) adding anhydrous zinc chloride to a beaker, taking concentrated hydrochloric acid with a glass pipette and dropping it into the beaker, slowly stirring until the anhydrous zinc chloride is completely dissolved, to obtain a mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid; after the temperature in step (1) drops to 32° C., continue stirring and slowly dropwise add the prepared mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid, and continue stirring at a temperature of 30° C. for 30 to 60 minutes;
[0037] (3) adding sodium hydroxide into deionized water and stirring to dissolve, preparing a sodium hydroxide solution with a mass fraction of 0.8%; after the stirring in step (2) is completed, continuing to stir and slowly adding the prepared sodium hydroxide solution dropwise, and after the addition is completed, continuing to stir for 30 to 60 minutes;
[0038] (4) After the stirring in step (3) is completed, continue stirring and slowly add the glyoxal solution dropwise. After the addition is complete, continue stirring for 30 to 60 minutes;
[0039] (5) After the stirring in step (4) is completed, continue stirring and add SPM-01. After the addition is complete, continue stirring for 30 to 60 minutes to obtain the product.
[0040] (6) Mixing the boric acid solution and the ethanol aqueous solution to obtain a mixed solution of the boric acid solution and the ethanol aqueous solution, and after the stirring in step (5) is completed, slowly adding dropwise the prepared mixed solution of the boric acid solution and the ethanol aqueous solution, and continuing stirring for 30 to 60 minutes to obtain the mixed solution.
[0041] Adopt the technical scheme of the present invention, the advantages are as follows:
[0042] The high-durability polarizer glue provided by the present invention selects polyvinyl alcohol Z-410, boric acid solution and ethanol aqueous solution as important components during the preparation process of the glue, and strictly controls the ratio of the components, so as to increase the molecular weight and reduce the gap between molecules, thereby overcoming the problems of poor water resistance and poor durability commonly existing in polarizers made of glue in the prior art, having good water resistance and durability, achieving a double 85 reliability test of more than 1000 hours, without blackening on all sides, and being suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 is a picture of the polarizer made of the glue of Example 1 immersed in a water bath at 80° C. for 4 hours;
[0044] Figure 2 This is a picture of the polarizer made of glue in comparative example 1 immersed in a water bath at 80°C for 4 hours;
[0045] Figure 3 This is a picture of the polarizer made of the glue in comparative example 3 immersed in a water bath at 80°C for 4 hours. DETAILED DESCRIPTION
[0046] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.
[0047] Example 1
[0048] A highly durable polarizer glue is prepared from the following components in parts by weight: 84 parts of deionized water, 4.5 parts of polyvinyl alcohol Z-410, 3 parts of SPM-01, 0.3 parts of anhydrous zinc chloride, 0.1 parts of concentrated hydrochloric acid, 0.03 parts of sodium hydroxide, 3.2 parts of glyoxal solution, 3.5 parts of boric acid solution and 1.37 parts of ethanol aqueous solution; wherein the mass fraction of concentrated hydrochloric acid is 36.5%; the mass fraction of glyoxal solution is 40%; the mass fraction of boric acid solution is 0.18%; and the mass fraction of ethanol aqueous solution is 95%;
[0049] The preparation process is as follows:
[0050] (1) Add deionized water to a beaker, keep it warm at 30°C and stir it evenly, then add polyvinyl alcohol Z-410 to the beaker in small amounts and multiple times until no lumps form. After adding, keep it warm at 30°C and stir it, then raise the temperature to 90°C and stir it for 1 to 2 hours; then cool it down to 32°C in a water bath;
[0051] (2) adding anhydrous zinc chloride to a beaker, taking concentrated hydrochloric acid with a glass pipette and dropping it into the beaker, slowly stirring until the anhydrous zinc chloride is completely dissolved, to obtain a mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid; after the temperature in step (1) drops to 32° C., continue stirring and slowly dropwise add the prepared mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid, and continue stirring at a temperature of 30° C. for 30 to 60 minutes;
[0052] (3) adding sodium hydroxide into deionized water and stirring to dissolve, preparing a sodium hydroxide solution with a mass fraction of 0.8%; after the stirring in step (2) is completed, continuing to stir and slowly adding the prepared sodium hydroxide solution (4 parts) dropwise, and after the addition is completed, continuing to stir for 30 to 60 minutes;
[0053] (4) After the stirring in step (3) is completed, continue stirring and slowly add the glyoxal solution dropwise. After the addition is complete, continue stirring for 30 to 60 minutes;
[0054] (5) After the stirring in step (4) is completed, continue stirring and add SPM-01. After the addition is complete, continue stirring for 30 to 60 minutes;
[0055] (6) Mixing the boric acid solution and the ethanol aqueous solution to obtain a mixed solution of the boric acid solution and the ethanol aqueous solution, and after the stirring in step (5) is completed, slowly adding dropwise the prepared mixed solution of the boric acid solution and the ethanol aqueous solution, and continuing stirring for 30 to 60 minutes to obtain the mixed solution.
[0056] Comparative Example 1
[0057] A highly durable polarizer glue is prepared from the following components in parts by weight: 84 parts of deionized water, 4.5 parts of polyvinyl alcohol Z-200, 3 parts of SPM-01, 0.3 parts of anhydrous zinc chloride, 0.1 parts of concentrated hydrochloric acid, 0.03 parts of sodium hydroxide, 3.2 parts of glyoxal solution, 3.5 parts of boric acid solution and 1.37 parts of ethanol aqueous solution; wherein the mass fraction of concentrated hydrochloric acid is 36.5%; the mass fraction of glyoxal solution is 40%; the mass fraction of boric acid solution is 0.18%; and the mass fraction of ethanol aqueous solution is 95%;
[0058] The preparation process is as follows:
[0059] (1) Add deionized water to a beaker, keep it warm at 30°C and stir it evenly, then add polyvinyl alcohol Z-200 to the beaker in small amounts and several times until no lumps form. After adding, keep it warm at 30°C and stir it, then raise the temperature to 90°C and stir it for 1 to 2 hours; then cool it down to 32°C in a water bath;
[0060] (2) adding anhydrous zinc chloride to a beaker, taking concentrated hydrochloric acid with a glass pipette and dropping it into the beaker, slowly stirring until the anhydrous zinc chloride is completely dissolved, to obtain a mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid; after the temperature in step (1) drops to 32° C., continue stirring and slowly dropwise add the prepared mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid, and continue stirring at a temperature of 30° C. for 30 to 60 minutes;
[0061] (3) adding sodium hydroxide into deionized water and stirring to dissolve, preparing a sodium hydroxide solution with a mass fraction of 0.8%; after the stirring in step (2) is completed, continuing to stir and slowly adding the prepared sodium hydroxide solution (4 parts) dropwise, and after the addition is completed, continuing to stir for 30 to 60 minutes;
[0062] (4) After the stirring in step (3) is completed, continue stirring and slowly add the glyoxal solution dropwise. After the addition is complete, continue stirring for 30 to 60 minutes;
[0063] (5) After the stirring in step (4) is completed, continue stirring and add SPM-01. After the addition is complete, continue stirring for 30 to 60 minutes;
[0064] (6) Mixing the boric acid solution and the ethanol aqueous solution to obtain a mixed solution of the boric acid solution and the ethanol aqueous solution, and after the stirring in step (5) is completed, slowly adding dropwise the prepared mixed solution of the boric acid solution and the ethanol aqueous solution, and continuing stirring for 30 to 60 minutes to obtain the mixed solution.
[0065] Comparative Example 2
[0066] A highly durable polarizer glue is prepared from the following components in parts by weight: 84 parts of deionized water, 4.5 parts of polyvinyl alcohol Z-410, 3 parts of SPM-01, 0.3 parts of anhydrous zinc chloride, 0.1 parts of concentrated hydrochloric acid, 0.03 parts of sodium hydroxide, 3.2 parts of glyoxal solution, 3.5 parts of boric acid solution and 1.37 parts of ethanol aqueous solution; wherein the mass fraction of concentrated hydrochloric acid is 36.5%; the mass fraction of glyoxal solution is 40%; and the mass fraction of boric acid solution is 0.18%;
[0067] The preparation process is as follows:
[0068] (1) Add deionized water to a beaker, keep it warm at 30°C and stir it evenly, then add polyvinyl alcohol Z-410 to the beaker in small amounts and multiple times until no lumps form. After adding, keep it warm at 30°C and stir it, then raise the temperature to 90°C and stir it for 1 to 2 hours; then cool it down to 32°C in a water bath;
[0069] (2) adding anhydrous zinc chloride to a beaker, taking concentrated hydrochloric acid with a glass pipette and dropping it into the beaker, slowly stirring until the anhydrous zinc chloride is completely dissolved, to obtain a mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid; after the temperature in step (1) drops to 32° C., continue stirring and slowly dropwise add the prepared mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid, and continue stirring at a temperature of 30° C. for 30 to 60 minutes;
[0070] (3) adding sodium hydroxide into deionized water and stirring to dissolve, preparing a sodium hydroxide solution with a mass fraction of 0.8%; after the stirring in step (2) is completed, continuing to stir and slowly adding the prepared sodium hydroxide solution (4 parts) dropwise, and after the addition is completed, continuing to stir for 30 to 60 minutes;
[0071] (4) After the stirring in step (3) is completed, continue stirring and slowly add the glyoxal solution dropwise. After the addition is complete, continue stirring for 30 to 60 minutes;
[0072] (5) After the stirring in step (4) is completed, continue stirring and add SPM-01. After the addition is complete, continue stirring for 30 to 60 minutes;
[0073] (6) After the stirring in step (5) is completed, slowly add the boric acid solution dropwise and continue stirring for 30 to 60 minutes to obtain the product.
[0074] Comparative Example 3
[0075] A highly durable polarizer glue is prepared from the following components in parts by weight: 84 parts of deionized water, 4.5 parts of polyvinyl alcohol Z-410, 3 parts of SPM-01, 0.3 parts of anhydrous zinc chloride, 0.1 parts of concentrated hydrochloric acid, 0.03 parts of sodium hydroxide, 3.2 parts of glyoxal solution, 3.5 parts of boric acid solution and 1.37 parts of ethanol aqueous solution; wherein the mass fraction of concentrated hydrochloric acid is 36.5%; the mass fraction of glyoxal solution is 40%; and the mass fraction of ethanol aqueous solution is 95%;
[0076] The preparation process is as follows:
[0077] (1) Add deionized water to a beaker, keep it warm at 30°C and stir it evenly, then add polyvinyl alcohol Z-410 to the beaker in small amounts and multiple times until no lumps form. After adding, keep it warm at 30°C and stir it, then raise the temperature to 90°C and stir it for 1 to 2 hours; then cool it down to 32°C in a water bath;
[0078] (2) adding anhydrous zinc chloride to a beaker, taking concentrated hydrochloric acid with a glass pipette and dropping it into the beaker, slowly stirring until the anhydrous zinc chloride is completely dissolved, to obtain a mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid; after the temperature in step (1) drops to 32° C., continue stirring and slowly dropwise add the prepared mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid, and continue stirring at a temperature of 30° C. for 30 to 60 minutes;
[0079] (3) adding sodium hydroxide into deionized water and stirring to dissolve, preparing a sodium hydroxide solution with a mass fraction of 0.8%; after the stirring in step (2) is completed, continuing to stir and slowly adding the prepared sodium hydroxide solution (4 parts) dropwise, and after the addition is completed, continuing to stir for 30 to 60 minutes;
[0080] (4) After the stirring in step (3) is completed, continue stirring and slowly add the glyoxal solution dropwise. After the addition is complete, continue stirring for 30 to 60 minutes;
[0081] (5) After the stirring in step (4) is completed, continue stirring and add SPM-01. After the addition is complete, continue stirring for 30 to 60 minutes;
[0082] (6) After the stirring in step (5) is completed, slowly add ethanol water solution and continue stirring for 30 to 60 minutes to obtain the obtained product. The test results after the glue is used on the polarizer are analyzed as follows:
[0083] After the glue in the embodiments and comparative examples was applied to the polarizer, it was immersed in a water bath at 80° C. for 1 to 4 hours to test the water resistance. The relevant experimental data are shown in Table 1.
[0084] Table 1 Water resistance data of the glue in the embodiments and comparative examples after being used on polarizers
[0085] Testing time Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 1 hour No change Black edge 0.5mm / Black edge 0.5mm 2 hours No change Black edge 1.0mm / Black edge 1.0mm 3 hours No change Black border 2.0mm / Black border 3.0mm 4 hours No change Black border 4.0mm / PVA shrinks severely
[0086] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that it is still possible to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on some of the technical features therein. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A highly durable polarizer glue, characterized in that: The invention is prepared from the following components in parts by weight: 80-92 parts of deionized water, 3-5 parts of polyvinyl alcohol Z-410, 2-5 parts of SPM-01, 0.1-0.5 parts of anhydrous zinc chloride, 0.05-0.15 parts of concentrated hydrochloric acid, 0.025-0.042 parts of sodium hydroxide, 1-5 parts of glyoxal solution, 1-5 parts of boric acid solution and 1-2 parts of ethanol aqueous solution. In its preparation process, polyvinyl alcohol is firstly stirred and dissolved in deionized water, and a mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid, sodium hydroxide solution, glyoxal solution, SPM-01, boric acid solution and ethanol aqueous solution are added, and stirred evenly to obtain the product.
2. The polarizer glue according to claim 1, characterized in that: The preparation of the polarizer glue comprises the following steps: (1) stirring and dissolving polyvinyl alcohol Z-410 in deionized water at 25-35° C., and after stirring and dissolving, continuing to heat up to 85-95° C. and stirring; (2) cooling down to 30-40° C., adding a prepared mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid, and stirring; (3) slowly dropping a prepared sodium hydroxide solution, and stirring; (4) adding a glyoxal solution, and stirring; (5) adding SPM-01 and stirring evenly; (6) adding the prepared mixed solution made of boric acid solution and ethanol aqueous solution and stirring evenly to obtain the product.
3. The highly durable polarizer glue according to claim 2, characterized in that: The polarizer glue is prepared from the following components in parts by weight: 82-88 parts of deionized water, 4-5 parts of polyvinyl alcohol Z-410, 2.5-3.5 parts of SPM-01, 0.25-0.35 parts of anhydrous zinc chloride, 0.08-0.12 parts of concentrated hydrochloric acid, 0.028-0.034 parts of sodium hydroxide, 2.5-3.5 parts of glyoxal solution, 3-4 parts of boric acid solution and 1.1-1.5 parts of ethanol aqueous solution.
4. The highly durable polarizer glue according to claim 3, characterized in that: The polarizer glue is made of the following components in parts by weight: 84 parts of deionized water, 4.5 parts of polyvinyl alcohol Z-410, 3 parts of SPM-01, 0.3 parts of anhydrous zinc chloride, 0.1 parts of concentrated hydrochloric acid, 0.03 parts of sodium hydroxide, 3.2 parts of glyoxal solution, 3.5 parts of boric acid solution and 1.37 parts of ethanol aqueous solution.
5. The glue for highly durable polarizer according to claim 4, characterized in that: The polyvinyl alcohol Z-410 is prepared by Nippon Synthetic Chemical Industry Co., Ltd.; the SPM-01 is prepared by Nippon Synthetic Chemical Industry Co., Ltd.
6. The highly durable polarizer glue according to claim 5, characterized in that: The mass fraction of the sodium hydroxide solution is 0.5-1%; the mass fraction of the concentrated hydrochloric acid is 36-38%; the mass fraction of the glyoxal solution is 35-45%; the mass fraction of the boric acid solution is 0.15-0.25%; and the mass fraction of the ethanol aqueous solution is 92-98%.
7. The highly durable polarizer glue according to claim 6, characterized in that: The mass fraction of the sodium hydroxide solution is 0.8%; the mass fraction of the concentrated hydrochloric acid is 36.5%; the mass fraction of the glyoxal solution is 40%; the mass fraction of the boric acid solution is 0.18%; and the mass fraction of the ethanol aqueous solution is 95%.
8. The method for preparing the highly durable polarizer glue according to claim 1, characterized in that: It includes the following steps: (1) Stir and dissolve polyvinyl alcohol Z-410 in deionized water at 25-35° C., and then continue to heat to 85-95° C. and stir; (2) Cooling to 30-40°C, adding a mixed solution of anhydrous zinc chloride and concentrated hydrochloric acid, and stirring; (3) slowly add the prepared sodium hydroxide solution dropwise and stir; (4) adding glyoxal solution and stirring; (5) Add SPM-01 and stir evenly; (6) Add the prepared mixed solution of boric acid solution and ethanol aqueous solution and stir evenly to obtain the product.
9. The method for preparing a highly durable polarizer glue according to claim 8, characterized in that: In step (1), polyvinyl alcohol Z-410 is stirred and dissolved in deionized water at 30° C.; after being stirred and dissolved, the temperature is continued to be raised to 90° C. and stirred for 0.5 to 3 hours; preferably, stirred for 1 to 2 hours.
10. The method for preparing a highly durable polarizer glue according to claim 8, characterized in that: In step (2), the temperature is lowered to 32° C. and the stirring time is 30 to 60 min; the mass fraction of the concentrated hydrochloric acid is 36 to 38%, preferably 36.5%; in step (3), the mass fraction of the sodium hydroxide solution is 0.5 to 1%, preferably 0.8%; and the stirring time is 30 to 60 min; in step (4), the mass fraction of the glyoxal solution is 35 to 45%, preferably 40%; and the stirring time is 30 to 60 min; in step (5), SPM-01 is added and the stirring time is 30 to 60 min; in step (6), the mass fraction of the boric acid solution is 0.15 to 0.25%, preferably 0.18%; the mass fraction of the ethanol aqueous solution is 92 to 98%, preferably 95%; and the stirring time is 30 to 60 min.
Citation Information
Patent Citations
Glue for polaroid and preparation method thereof
CN113502136A